[Ga3+8Sm3+2, Ga3+8Tb3+2] Metallacrowns are Highly Promising Ratiometric Luminescent Molecular Nanothermometers Operating at Physiologically Relevant Temperatures. Issue 61 (29th September 2020) - Salerno, Elvin V.; Zeler, Justyna; Eliseeva, Svetlana V.; Hernández‐Rodríguez, Miguel A.; Carneiro Neto, Albano N.; Petoud, Stéphane; Pecoraro, Vincent L.; Carlos, Luís D.
Abstract: Nanothermometry is the study of temperature at the submicron scale with a broad range of potential applications, such as cellular studies or electronics. Molecular luminescent‐based nanothermometers offer a non‐contact means to record these temperatures with high spatial resolution and thermal sensitivity. A luminescent‐based molecular thermometer comprised of visible‐emitting Ga 3+ /Tb 3+ and Ga 3+ /Sm 3+ metallacrowns (MCs) achieved remarkable relative thermal sensitivity associated with very low temperature uncertainty of S r = 1.9 % K −1 and δT <0.045 K, respectively, at 328 K, as an aqueous suspension of polystyrene nanobeads loaded with the corresponding MCs. To date, they are the ratiometric molecular nanothermometers offering the highest level of sensitivity in the physiologically relevant temperature range. Abstract : Metallacrown‐based thermometry : Mixtures of luminescent Ga 3+ /Tb 3+ and Ga 3+ /Sm 3+ metallacrowns proved to be highly sensitive luminescent molecular thermometers. These were placed in polystyrene nanobeads for aqueous stabilization and demonstrate the promise of a molecular approach to nanothermometry.